Relevansi Peranan Hukum Adat Terhadap Pembaharuan Hukum di Indonesia - Asti Ichtiarini (CV. Lenggogeni Data Publishing, 2024)
This article aims to find out and describe in detail the history of the birth of customary law in Indonesia, as well as understanding the importance of customary law in legal reform in Indonesia. This research is research using a normative juridical approach method, as well as a legal study approach (legal philosophy), namely Sociological Jurisprudence. Based on the results of the discussion, it can be explained that customary law was first popularized by Snouck Hurgronje in 1893. Customary law or Adatrecht is a law whose application was intended for the Bumiputera or Indonesian group as well as the Foreign East group during the Dutch East Indies colonial period. Customary Law began to be officially recognized by the Dutch Colonial government and was parallel to European Law or Western Law through Article 131 paragraph (6) of the Indische Staatsregeling (IS). Through this article, Customary Law is declared as a source of positive law for the Indonesian nation. The role of customary law in Indonesia before the amendment was less clear in terms of recognition and use, but after reviewing it, it can be concluded that the existing formulation contains the noble values ​​and spirit of customary law. After the constitutional amendment, customary law was recognized as stated in the 1945 Constitution Article 18D paragraph 2 so that it became one of the laws that was officially used apart from the use of laws and regulations made by the government. Customary law has the same function and goal, namely justice, social control, and seeking benefit as a common goal. Customary law can be used to resolve problems related to land, inheritance rights, etc. Abstrak Artikel ini bertujuan untuk mengetahui dan mendeskripsikan secara rinci mengenai sejarah lahirnya hukum adat di Indonesia, serta memahami peranan hukum adat terhadap pembaharuan hukum di Indonesia. Penelitian ini merupakan penelitian dengan metode pendekatan yuridis normatif, serta pendekatan kajian hukum (filsafat hukum) yaitu Sociological Jurisprudence. Berdasarkan hasil pembahasan dapat dijelaskan bahwa hukum adat dipopulerkan pertama kali oleh Snouck Hurgronje pada tahun 1893. Hukum adat atau Adatrecht merupakan hukum yang keberlakuannya diperuntukkan untuk golongan Bumiputera atau Indonesia serta golongan Timur Asing pada masa penjajahan Hindia Belanda. Hukum Adat mulai diakui secara resmi oleh pemerintah Kolonial Belanda dan sejajar kedudukannya dengan Hukum Eropa atau Hukum Barat melalui Pasal 131 ayat (6) Indische Staatsregeling (IS). Melalui pasal ini pula, Hukum Adat dinyatakan sebagai sumber hukum positif bagi bangsa Indonesia. Peranan hukum adat di Indonesia pada saat sebelum amandemen kurang tegas dalam hal pengakuan dan pemakaian, namun setelah ditelaah dapat disimpulkan bahwa rumusan yang ada mengandung nilai luhur dan jiwa hukum adat. Setelah amandemen konstitusi, hukum adat diakui sebagaimana dinyatakan dalam UUD 1945 Pasal 18D ayat 2 sehingga menjadi salah satu hukum yang resmi digunakan disamping penggunaan hukum dan peraturan yang dibuat oleh pemerintah. Hukum adat memiliki fungsi dan tujuan yang sama yaitu untuk keadilan, pengendalian sosial, dan mengusahakn kemaslahatan sebagai tujuan bersama. Hukum adat dapat dipergunakan dalam penyelesaian masalah-masalah yang berkaitan dengan tanah, hak waris, dan lain-lain. Kata Kunci: relevansi, hukum adat, pembaharuan hukum